Forma urbana tradicional e modernista: Uma reflexão sobre o uso e estética dos espaços urbanos (ARQUISUR Revista, 2015)
The objective of this paper is to discuss some of the implications of traditional urban form and modernist urban form, for the use and aesthetics of urban spaces, such as the existence of visual and functional connections between buildings and public open spaces and the use given to the ground floors. In "traditional urban form" the buildings have front doors and windows facing public streets, while in the "modernist urban form" buildings tend to have doors and windows distant from public streets and/or directed to internal open spaces in the block, without distinction between front and back doors and windows. Thus, examples of cities in different countries are used for comparisons and reflections involving these aspects. The main consequences of these analyzes reinforce the need for a better understanding on the implications of urban form for the use and aesthetics of urban spaces. Additionally, it is highlighted the importance of visual and functional connections between the ground floor and the public open spaces, to the vitality, safety and appearance of urban spaces.
Keywords: desenho urbano; estética urbana; modernismo; uso dos espaços urbanos; vitalidade urbana